EVALUATION OF ANTIOXIDANT PROPERTIES, TOTAL PHENOLIC AND FLAVONOID CONTENT OF SIX MEDICINAL PLANTS - SUBRAHMANIYAN, MEETHU; MANGANG, IRENGBAM BARUN; MANICKAM, LOGANATHAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The medicinal plants, Aloe vera (Kattarvazha), Ocimum tenuiflourm (Tulsi), Azadirachta indica (Neem), Thymus vulgaris (Thyme), Piper betel (Betel leaf), Acalypha indica (Kuppaimeni) were selected for management of stored grain pest management. The antioxidant activity, total phenolic and total flavonoid content of these six medicinal plant extracts were evaluated by using DPPH free radical, Folin-Ciocalteu and Aluminium chloride method, respectively. The total Phenolic content of the extracts was determined spectrophotometrically according to the Folin-Ciocalteu procedure and ranged from 127.0 mg/g to 339.6 mg/g on fresh leaves basis. The total flavanoid content of extracts were determined by aluminium chloride colorimetric assay and the values ranged from 0.16 mg/g to 4.00 mg/g of fresh weight. The results showed that the betel leaf extracts in acetone have highest (80.35%) DPPH Scavenging activity. The use of these plant extracts for the pest management in storage facilities may provide additional medicinal values to stored food commodities.